Answer:
![\left(g\:\circ \:\:\:h\right)\left(-4\right)=-2](https://img.qammunity.org/2022/formulas/mathematics/high-school/uez0d493lul4y6qq1ufdv8nf1r4jaeacy4.png)
Hence, option B) is true.
Explanation:
Given
g(t) = t² - 2
h(t) = t + 4
To determine
![\left(g\:\circ \:\:h\right)\left(-4\right)=?](https://img.qammunity.org/2022/formulas/mathematics/high-school/zott8efzxtfcogezi1g6q4tmjm2kzxcaxq.png)
Using the formula
![\left(g\:\circ \:\:h\right)\left(-4\right)\:=g\left(h\left(-4\right)\right)](https://img.qammunity.org/2022/formulas/mathematics/high-school/qqicfvmjpnc8txeqwvoiac86sq0bnkn0a3.png)
In order to determine g(h(-4)), first we need to determine h(-4), so
substituting t = -4 in h(t) = t + 4
h(t) = t + 4
h(-4) = -4 + 4
h(-4) = 0
so we can write
![\left(g\:\circ \:\:\:h\right)\left(-4\right)\:=g\left(h\left(-4\right)\right)=g\left(0\right)](https://img.qammunity.org/2022/formulas/mathematics/high-school/7h5kyw1qrq232xwd4lui825zhfcqrm8xpl.png)
now, to determine g(0), substitute t = 0 in g(t) = t² - 2v
g(t) = t² - 2
g(0) = (0)² - 2
g(0) = 0 - 2
g(0) = -2
so, finally we get
![\left(g\:\circ \:\:\:h\right)\left(-4\right)\:=g\left(h\left(-4\right)\right)=g\left(0\right)=-2](https://img.qammunity.org/2022/formulas/mathematics/high-school/dtcmokzmpy5hreuiaguamtvyrlmqudzqfz.png)
Therefore,
![\left(g\:\circ \:\:\:h\right)\left(-4\right)=-2](https://img.qammunity.org/2022/formulas/mathematics/high-school/uez0d493lul4y6qq1ufdv8nf1r4jaeacy4.png)
Hence, option B) is true.